Analysis of Mobile Village Development Innovation in Technology-Based Public Services - Aliffina Nurhariska; Hayat Hayat; Agus Zainal Abidin (Jurnal Manajemen Pelayanan Publik, 2023)
The implementation of public services in village government often experiences problems with timeliness, transparency, and effectiveness in services. So that technology-based public service innovation is needed to support this progress. The purpose of this writing is to analyze and identify the performance of the Saiti Mobile application used in public services in Saiti Village. In addition to discussing the performance of these applications, this paper also explains the elements of the benefits and satisfaction of public services received by the community from the development of this technology. This research was conducted using a qualitative approach with data collection techniques in the form of in-depth interviews, participant observation, and documentation. Based on the results of the research that has been done, it shows that the application of the Saiti Mobile application in Saiti Village is very helpful and beneficial for the community because it can increase trust, efficiency and effectiveness in services in Saiti Village.